2015
DOI: 10.1111/clr.12625
|View full text |Cite
|
Sign up to set email alerts
|

Guided bone regeneration of peri‐implant defects with particulated and block xenogenic bone substitutes

Abstract: AIM To test whether an equine bone substitute block used for guided bone regeneration (GBR) of peri-implant defects renders different results from bovine block or particulated bone substitutes regarding the dimensions of the augmented ridge and the amount of new bone. MATERIAL AND METHODS Mandibular premolars and molars were extracted in eight dogs. After 4 months, four semisaddle bone defects were created in each mandible and one titanium implant was inserted into every site. Bone augmentation by GBR was atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
102
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(111 citation statements)
references
References 25 publications
5
102
1
3
Order By: Relevance
“…On the other hand SR has shown an increase in the alkaline phosphatase activity which is a marker for an increase in collagen synthesis and osteoblast differentiation. This supports the result which shows an improvement of the primary stability to the secondary stability (Canalis et al, 1996;Barbara et al, 2004;Kim et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand SR has shown an increase in the alkaline phosphatase activity which is a marker for an increase in collagen synthesis and osteoblast differentiation. This supports the result which shows an improvement of the primary stability to the secondary stability (Canalis et al, 1996;Barbara et al, 2004;Kim et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…As from the results of the present study, alveolar ridge augmentation and Strontium Renalate following immediate implant placement have shown to provide good primary and secondary stability (Benic et al, 2016). The study, showed a highly statistically significant difference in the primary and secondary stability values in Group A (Alveolar ridge augmentation), even though the procedure was technique sensitive and is similar to the results that single-stage implant placement and simultaneous grafting with mineralized particulate allograft showed promising outcome in correcting small and medium sized vertical labial wall defects.…”
Section: Discussionsupporting
confidence: 66%
“…Due to the size of the defect and thereby a further need of stability of the augmentation in the present study, the DBBM block was used. These blocks have shown a rather poor ingrowth of bone in a pre‐clinical study, but appeared to be efficient in keeping the augmented dimension (Benic et al., ). Apart from this, a clinical case series demonstrated successful primary augmentation using the same DBBM block material.…”
Section: Discussionmentioning
confidence: 99%
“…Another analysis performed in the canine mandible showed that bovine bone blocks stabilizing a collagen membrane yielded less soft tissue ingrowth than the same material used as particulate graft under the same membrane (Benic et al. ).…”
Section: Discussionmentioning
confidence: 99%